Awareness of hypertensive retinopathy among hypertension patient in Selangor / Faris Abdul Kadir @ Lokman - Abdul Kadir @ Lokman, Faris (Faculty of Health Sciences, 2015)
Purpose: Hypertension is a worldwide problem that contributes to other diseases such as cardiovascular diseases and also ocular diseases. Unfortunately, hypertensive awareness, remain less than optimal. The simplest method to determine the awareness of hypertension retinopathy can be achieve by completing questionnaire. Thus this study was conducted to identify the level of awareness of hypertensive retinopathy.Methods: Sixty four of hypertension patients 37 male and 27 female were assigned into this study where they need to answer 2 set of questionaire. All questionaires were collected as soon as subject finished answering the questions. Result: The questionaire of this research show good validity based on content and face validation done during pilot study. Overall the awareness of the hyperensive retinopathy were low with 23.4% aware about hypertensive retinopathy. Conclusion: Awareness of hypertensive retinopathy still low among hypertension patient in Selangor area. More research about this topic need to be done in order to increases the awareness of hypertensive retinopathy